Si PeKA “Sistem Pengolah Kedisiplinan Anak" - Alwati Alwati; Dini Kartika Ansyari; Khalista Aqilla Mude; Aditya Wahyu Purnama; Safrizal Safrizal (ABDI SABHA (Jurnal Pengabdian kepada Masyarakat), 2020)
The purpose of this service is to introduce and implement The sensitive "Processing System Child Discipline" in Orphanage Ar-Rahim as a solution to discipline problems in foster care. As for the background of this devotion for the average orphanage located in Pekanbaru coined the low level of discipline. This we know when we visit some orphanages are in Pekanbaru. low levels ofdiscipline in children resulting in the quality of the child's self to be low in order to compete in the future. Seeing that we create a system that we named "The-sensitive" child discipline processing system in which the system uses daily activity form is packaged into a software-application. The applications are not just used by the orphanage, but educational institutions can use it. The method used in this devotion is the method of discussion and workshops, by doing debriefing and providing motivation to the orphans of the discipline, while the valuation method is through a pre-test and post, and also daily form 14 days. The results found from these activities in the form of qualitative and quantitative. Qualitatively orphans declare any change perceived after the program is run by a team of Si sensitive. Quantitatively the increased amount of discipline of children at home Ar-Rahim. This is evidenced significant change between the results obtained with the answer of the orphanage children.